Memorizing the Qur’an for Busy People: A Study of the Contribution of T.E.S. (Tilâwah Evaluasi Sederhana) Method in Enhancing Memorization of the Qur’an - Cucu Surahman; Mokh. Iman Firmansyah; Muhamad Parhan; Ahmad Hakam (KARSA Journal of Social and Islamic Culture, 2025)
Facts show memorizing the Qur’an is difficult, especially considering contemporary man’s busyness. The memorizers of the Qur’an admit that they have difficulty finding time to repeat (murâja’ah) the memorizations they have consistently. This study tries to reveal the contribution of the T.E.S. method, a method of memorizing the Qur’an discovered by Ustadz Jemmi Gumilar ST., in improving the memorization of the Qur’an. Using a qualitative approach and descriptive method, this study shows that the T.E.S. method has positively contributed to improving the quality and quantity of memorization of the Qur’an of the tahfîzh participants. Many beneficiaries and recognition of the training participants for the effectiveness of the T.E.S. method prove this. Theoretically, the success of the T.E.S. method lies in time management and discipline or consistency in reading the Qur’an, memorizing, and repeating memorization.